Light Fields for Minimal Invasive Surgery Using an Endoscope Positioning Robot - Vogt, F.; Krüger, S.; Schmidt, J.; Paulus, D.; Niemann, H.; Hohenberger, W.; Schick, C. H. (Methods of Information in Medicine, 2004)
Objectives: To generate a fast and robust 3-D visualization of the operation site during minimal invasive surgery.Methods: Light fields are used to model and visualize the 3-D operation site during minimal invasive surgery. An endoscope positioning robot provides the position and orientation of the endoscope. The a priori unknown transformation from the endoscope plug to the endoscope tip (hand-eye transformation) can either be determined by a three-step algorithm, which includes measuring the endoscope length by hand or by using an automatic hand-eye calibration algorithm. Both methods are described in this paper and their respective computation times and accuracies are compared.Results: Light fields were generated during real operations and in the laboratory. The comparison of the two methods to determine the unknown hand-eye transformation was done in the laboratory. The results which are being presented in this paper are: rendered images from the generated light fields, the calculated extrinsic camera parameters and their accuracies with respect to the applied hand-eye calibration method, and computation times.Conclusion: Using an endoscope positioning robot and knowing the hand-eye transformation, the fast and robust generation of light fields for minimal invasive surgery is possible.
Keywords: Light field; hand-eye calibration; minimally invasive surgical procedures; endoscopy; 3-D visualization